Investigation on the impact of learning mathematics using mobile phones at higher institutions in a Tanzanian context - Emmanuel Deogratias; Festo Focus; Emmanuel Matumba (Universitas Sarjanawiyata Tamansiswa, 2025)
This paper presents the impact of learning mathematics using mobile phones at higher institutions in a Tanzanian context. The quantitative approach was employed in this study for numerical data collection. Two hundred and five students participated in this study. A questionnaire was used while collecting data. Content analysis was used in the analysis process of the collected data. The tools used to analyze data included statistical software such as SPSS, a high-performance programming language and numerical computing environment developed by MathWorks. It was found that a large number of students frequently use mobile phones in learning mathematics. Also, mobile phones help students improve their understanding of mathematical concepts, including solving mathematical problems. They also help students collaborate with their peers while learning mathematics. From the results, using mobile phones supports students to enhance their learning of mathematics in university mathematics classrooms. The study concludes that mobile phone usage has a significant positive impact on students’ mathematics learning by facilitating problem-solving, conceptual understanding, engagement, and collaboration. Furthermore, this research contributes valuable insights to support policymakers and educators in developing strategies and professional development programs for effective mobile learning integration in Tanzanian higher education.